Salmonella enterica serovar Typhi plasmid pR ST98 enhances intracellular bacterial growth and S. typhi-induced macrophage cell death by suppressing autophagy - He,Peiyan (2012)
OBJECTIVES: Plasmid pR ST98 is a hybrid resistance-virulence plasmid isolated from Salmonella enterica serovar Typhi (S. typhi). Previous studies demonstrated that pR ST98 could enhance the virulence of its host bacteria. However, the mechanism of pR ST98-increased bacterial virulence is still not fully elucidated. This study was designed to gain further insight into the roles of pR ST98 in host responses. METHODS: Human-derived macrophage-like cell line THP-1 was infected with wild-type (ST8), pR ST98-deletion (ST8-ΔpR ST98), and complemented (ST8-c-pR ST98) S. typhi strains. Macrophage autophagy was performed by extracting the membrane-unbound LC3-I protein from cells, followed by flow cytometric detection of the membrane-associated fraction of LC3-II. Intracellular bacterial growth was determined by colony-forming units (cfu) assay. Macrophage cell death was measured by flow cytometry after propidium iodide (PI) staining. Autophagy activator rapamycin (RAPA) was added to the medium 2 h before infection to investigate the effect of autophagy on intracellular bacterial growth and macrophage cell death after S. typhi infection. RESULTS: Plasmid pR ST98 suppressed autophagy in infected macrophages and enhanced intracellular bacterial growth and S. typhi-induced macrophage cell death. Pretreatment with RAPA effectively restricted intracellular bacterial growth of ST8 and ST8-c-pR ST98, and alleviated ST8 and ST8-c-pR ST98-induced macrophage cell death, but had no significant effect on ST8-ΔpR ST98. CONCLUSIONS: Plasmid pR ST98 enhances intracellular bacterial growth and S. typhi-induced macrophage cell death by suppressing autophagy.